Environment Reporting in Annual Reports: A Comparative Analysis of Reporting Practices of Listed Firms in Nigeria - Akparhuere, Godwin Oghenekohwo (Archives of Business Research, 2019)
Environment reporting practice is a relatively new concept with a global affirmation and sanction. It requires transparency and sincerity of disclosure among the practicing firms and as required under the law. The broad objective of this study is to carry out a comparative analysis of reporting practices and its effect on performance (proxy by total assets) of listed oil and gas firms on the one hand and consumer goods firms in Nigeria (on the other hand). The study adopted the ex-post facto research design whereby existing and published data of reporting companies have been sought through their annual reports. Data for analyses were obtained through secondary sources, namely, the annual reports and accounts of the sampled companies. The Nigerian oil and gas subsector has 12 listed firms while the manufacturing sub-sector has 31 companies, from which three firms each (total of six) were sampled for the study. The purposive sampling technique was adopted in the choice of firm to be included in the study; Mobil oil and gas, MRS Oil Nig plc and Total Nig plc were chosen from the oil and gas sector while Nestle Nig plc, Nigerian Breweries plc, and Dangote flour Mills were selected from the consumer goods industry. The analyses adopted the use of SPSS version 20.0 and the essential tools were the correlation coefficient, the coefficient of determination and the simple regression analysis model. It was found that discretionary social responsibility reporting practices (donations and gifts) have significant effects on performance of both oil and gas firms and consumer goods companies in Nigeria. The study recommends that firms should consolidate on discretionary SR practices to ward off restiveness in the communities where they operate.